Incidence- and In-hospital Mortality-Related Risk Factors of Acute Kidney Injury Requiring Continuous Renal Replacement Therapy in Patients Undergoing Surgery for Acute Type a Aortic Dissection - Chen, Xuelian; Zhou, Jiaojiao; Fang, Miao; Yang, Jia; Wang, Xin; Wang, Siwen; Li, Linji; Zhu, Tao; Ji, Ling; Yang, Lichuan (Frontiers in Cardiovascular Medicine, 2021)
Background: Few studies on the risk factors for postoperative continuous renal replacement therapy (CRRT) in a homogeneous population of patients with acute type A aortic dissection (AAAD). This retrospective analysis aimed to investigate the risk factors for CRRT and in-hospital mortality in the patients undergoing AAAD surgery and to discuss the perioperative comorbidities and short-term outcomes. Methods: The study collected electronic medical records and laboratory data from 432 patients undergoing surgery for AAAD between March 2009 and June 2021. All the patients were divided into CRRT and non-CRRT groups; those in the CRRT group were divided into the survivor and non-survivor groups. The univariable and multivariable analyses were used to identify the independent risk factors for CRRT and in-hospital mortality. Results: The proportion of requiring CRRT and in-hospital mortality in the patients with CRRT was 14.6 and 46.0%, respectively. Baseline serum creatinine (SCr) [odds ratio (OR), 1.006], cystatin C (OR, 1.438), lung infection (OR, 2.292), second thoracotomy (OR, 5.185), diabetes mellitus (OR, 6.868), AKI stage 2–3 (OR, 22.901) were the independent risk factors for receiving CRRT. In-hospital mortality in the CRRT group (46%) was 4.6 times higher than in the non-CRRT group (10%). In the non-survivor (n = 29) and survivor (n = 34) groups, New York Heart Association (NYHA) class III-IV (OR, 10.272, P = 0.019), lactic acidosis (OR, 10.224, P = 0.019) were the independent risk factors for in-hospital mortality in patients receiving CRRT. Conclusion: There was a high rate of CRRT requirement and high in-hospital mortality after AAAD surgery. The risk factors for CRRT and in-hospital mortality in the patients undergoing AAAD surgery were determined to help identify the high-risk patients and make appropriate clinical decisions. Further randomized controlled studies are urgently needed to establish the risk factors for CRRT and in-hospital mortality.